Leaving care in Scotland: the residential experience - Jo Dixon; Mike Stein (Scottish Journal of Residential Child Care)
Each year over a thousand young people aged sixteen and over leave care in Scotland. What does leaving care mean for these young people and what happens to them in the early stages of post-care living? What has helped them to prepare for leaving care and how best can they be supported to achieve positive outcomes as they continue their transition to independent living? These questions formed the basis of a recent survey of young people who had moved on from the care of three Scottish local authorities (Dixon and Stein, 2002a; 2002b)